2010
DOI: 10.1186/1471-2288-10-110
|View full text |Cite
|
Sign up to set email alerts
|

Involving users in the design of a randomised controlled trial of an intervention to promote early presentation in breast cancer: qualitative study

Abstract: BackgroundThe purpose of this study was to explore women's views of the design of a large pragmatic cost-effectiveness randomised controlled trial of the policy of offering a health professional-delivered intervention to promote early presentation with breast symptoms in older women and thereby improve survival, with a view to informing protocol development. The trial will recruit over 100,000 healthy women aged 67+, and outcome data will be collected on those who develop breast cancer. The scale of the trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…The search covered two main areas of research: firstly, patient and clinical staff attitudes to RCTs and secondly, patient and clinical staff attitudes to venous access devices. Many qualitative studies have explored the views of cancer patients to the process of RCTs, exploring informed consent (12,13), understanding of equipoise (14), randomisation (15), recruitment (13,14,16) and participation in trial design (17). Despite this, recent research reveals health professionals' discomfort at approaching patients to discuss participation in an RCT at an already stressful period for the patient (17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search covered two main areas of research: firstly, patient and clinical staff attitudes to RCTs and secondly, patient and clinical staff attitudes to venous access devices. Many qualitative studies have explored the views of cancer patients to the process of RCTs, exploring informed consent (12,13), understanding of equipoise (14), randomisation (15), recruitment (13,14,16) and participation in trial design (17). Despite this, recent research reveals health professionals' discomfort at approaching patients to discuss participation in an RCT at an already stressful period for the patient (17).…”
Section: Methodsmentioning
confidence: 99%
“…Many qualitative studies have explored the views of cancer patients to the process of RCTs, exploring informed consent (12,13), understanding of equipoise (14), randomisation (15), recruitment (13,14,16) and participation in trial design (17). Despite this, recent research reveals health professionals' discomfort at approaching patients to discuss participation in an RCT at an already stressful period for the patient (17). In addition, whilst several qualitative studies examine patient experiences of a single device (18)(19)(20)(21)(22)(23), few examine patients' attitudes to device choice; those which do, focus on educational and information needs in relation to device selection (24,25).…”
Section: Methodsmentioning
confidence: 99%
“…Several researchers have identified that PPI has helped them address ethical dilemmas, 17,71,78,85,91 for example ethically appropriate ways of contacting women with recently diagnosed breast cancer and the use of routine patient data. 92 There is also some suggestion that lay co-researchers have a role to play in helping safeguard potentially vulnerable participants. 82 The impact of PPI has a moral dimension in the reported outcomes for service users and the public involved in the study.…”
Section: Patient and Public Involvement: The Methodological Argumentmentioning
confidence: 99%
“…Forty additional publications were retrieved reporting their needs assessment (n = 18), their step 4 (n = 3), their implementation planning (n = 1), their evaluation (n = 17), and their implementation (n = 1).…”
Section: Resultsmentioning
confidence: 99%